Immunoregulation: the interplay between metabolism and redox homeostasis - Perpiñán, E.; Sanchez-Fueyo, A.; Safinia, N. (Frontiers in Transplantation, 2023)
Regulatory T cells are fundamental for the induction and maintenance of immune homeostasis, with their dysfunction resulting in uncontrolled immune responses and tissue destruction predisposing to autoimmunity, transplant rejection and several inflammatory and metabolic disorders. Recent discoveries have demonstrated that metabolic processes and mitochondrial function are critical for the appropriate functioning of these cells in health, with their metabolic adaptation, influenced by microenvironmental factors, seen in several pathological processes. Upon activation regulatory T cells rearrange their oxidationreduction (redox) system, which in turn supports their metabolic reprogramming, adding a layer of complexity to our understanding of cellular metabolism. Here we review the literature surrounding redox homeostasis and metabolism of regulatory T cells to highlight new mechanistic insights of these interlinked pathways in immune regulation.